Food security and diet quality among urban poor adolescents in Kuala Lumpur, Malaysia - Ee, Janice Fang Tay; Kaur, Satvinder; Wui, Wui Tham; Wan, Ying Gan; Che Ya, Nik Norasma; Choon, Hui Tan; En, Serene Hui Tung (The Korean Nutrition Society and the Korean Society of Community Nutrition, 2023)
BACKGROUND/OBJECTIVES This study aimed to examine the food security status of urban poor adolescents and its association with diet quality.